Usability Analysis of The Website of The Housing and Settlement Area Office of The District of South Bengkulu - heriadi, wiwin (Internet of Things and Artificial Intelligence Journal, 2024)
The Bengkulu Selatan Regency Government has developed e-government by providing various information channels through websites throughout the Regional Apparatus Organizations (OPD), in this case, the Housing and Settlement Service. Usability assessment is needed to support further development and determine the value of the benefits of e-government to meet the community's needs. There are 4 aspects evaluated in this study, namely 4 aspects: usability, System Usefulness, Information Quality, Interface Quality, and Overall. This study uses the Post Study System Usability Questionnaire (PSSUQ) method, namely a questionnaire used to assess a system or to determine the extent of user experience to get a comprehensive impression of the user experience or end user of a system with a case study of the website of the Housing and Settlement Service of Bengkulu Selatan Regency. The results of the website usability research obtained the Usefulness aspect value (System Usefulness) with an average value of 2.26, the Information Quality aspect (Information Quality) with a value of 2.03, and Interface Quality (Interface Quality) with an average value of 1.91 and Overall (Overall) with a value of 2.11 where the lower limit of the PSSUQ norm is 2.62.